Amplification Factors in the Case of Beam Under Moving Force – Theoretical Analysis - Ataman M. (Archives of Civil Engineering, 2019)
The impact of a moving load speed on the dynamic overload of beams, assuming that the track of the load has no unevenness, is examined. First the problem of a visco-elastic beam on a Winkler foundation subjected to a force moving at a constant speed will be solved. Using the Bubnov-Galerkin method, the deflections of the beam, and then the bending moments and shear forces will be determined. The solution of the problem will be obtained both for the case of a forced vibration and the case of a free vibration after the moving force has left the beam. Using these solutions, dynamic amplification factors will be determined for the deflections, bending moments, and shear forces, which are different for the two cases.